Toll-Like Receptor 4 (TLR4) and AMPK Relevance in Cardiovascular Disease - Haleh Vaez; Hamid Soraya; Alireza Garjani; Tooba Gholikhani (Tabriz University of Medical Sciences, 2023)
Toll-like receptors (TLRs) are essential receptors of the innate immune system, playing a significant role in cardiovascular diseases. TLR4, with the highest expression among TLRs in the heart, has been investigated extensively for its critical role in different myocardial inflammatory conditions. Studies suggest that inhibition of TLR4 signaling pathways reduces inflammatory responses and even prevents additional injuries to the already damaged myocardium. Recent research results have led to a hypothesis that there may be a relation between TLR4 expression and 5' adenosine monophosphate-activated protein kinase (AMPK) signaling in various inflammatory conditions, including cardiovascular diseases. AMPK, as a cellular energy sensor, has been reported to show anti-inflammatory effects in various models of inflammatory diseases. AMPK, in addition to its physiological acts in the heart, plays an essential role in myocardial ischemia and hypoxia by activating various energy production pathways. Herein we will discuss the role of TLR4 and AMPK in cardiovascular diseases and a possible relation between TLRs and AMPK as a novel therapeutic target. In our opinion, AMPK-related TLR modulators will find application in treating different immune-mediated inflammatory disorders, especially inflammatory cardiac diseases, and present an option that will be widely used in clinical practice in the future.